2017
DOI: 10.5194/bg-2017-89
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substrate potential of Eemian to Holocene permafrost organic matter for future microbial greenhouse gas production

Abstract: Abstract. Multiple permafrost cores from Bol´shoy Lyakhovsky Island in NE Siberia comprising deposits from Eemian to modern time are investigated to evaluate the stored potential of the freeze-locked organic matter (OM) to serve as substrate 10 for the production of microbial greenhouse gases from thawing permafrost deposits. Deposits from Late Pleistocene glacial periods (comprising MIS 3 and MIS 4) possess an increased aliphatic character and a higher amount of potential substrates, and therefore higher OM q… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…4A), implying the presence of methanogenic Euryarchaeota (Blaga et al, 2008). This agrees well with the detection of archaeol in the Bol'shoy Lyakhovsky Island L14 cores by Stapel et al (2018) and archaeol in a drill core from Kurungnakh Island investigated by Bischoff et al (2013). Additionally, mean GDGT-2/crenarchaeol ratios are !0.2 in active layer soils, Holocene fluvial terrace/floodplain sediments, and Yedoma ( Fig.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…4A), implying the presence of methanogenic Euryarchaeota (Blaga et al, 2008). This agrees well with the detection of archaeol in the Bol'shoy Lyakhovsky Island L14 cores by Stapel et al (2018) and archaeol in a drill core from Kurungnakh Island investigated by Bischoff et al (2013). Additionally, mean GDGT-2/crenarchaeol ratios are !0.2 in active layer soils, Holocene fluvial terrace/floodplain sediments, and Yedoma ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Drill cores L14-02, L14-04, and L14-05 were retrieved from Bol'shoy Lyakhovsky Island. L14-02 includes a late Pleistocene Ice Complex sequence (MIS 3) while L14-04 and L14-05 represent interglacial thermokarst sediments from the Eemian (MIS 5) and interstadial deposits from the late Pleistocene (MIS 4 and MIS 3) and Holocene, respectively (Stapel et al, 2018). Each of the Buor Khaya Peninsula and Bol'shoy Lyakhovsky Island drill cores included an uppermost active layer soil.…”
Section: Site Description and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a yedoma permafrost core collected from northeast Siberia, sediments deposited during climatic conditions of the late Pleistocene glacial periods had increased aliphatic and acetate concentrations compared to sediments from the same core deposited during interglacial periods and the Holocene (Stapel et al, ). The sediments deposited during glacial periods also had higher abundances of biomarkers for past microbial communities, suggesting that the increased aliphatic and acetate concentrations may have also been influenced by climatic conditions and microbial processing during deposition (Stapel et al, , ). At the VC permafrost tunnel, paleobotanical proxy data from our sampled depths suggest that climatic conditions at the time of sediment deposition were relatively warm, wet, and similar to Holocene conditions (Schirrmeister et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Yedoma cores collected from similar depths to our study from near Livengood, AL show increasing acetate concentrations with sediment age (Ewing et al, 2015), suggesting that the variation in WEOM composition we observed at the VC permafrost tunnel may be due to processing following permafrost formation. Each of these studies (this study; Ewing et al, 2015;Stapel et al, 2016Stapel et al, , 2017 point to the importance of OM processing, both during Values are mean (SD) cumulative C mineralization among triplicate vials during the 154-day incubation. a CE = carbon equivalent.…”
Section: 1029/2018jg004712mentioning
confidence: 99%